Robust autoactivation, chymotrypsin C independence and diminished secretion define a subset of hereditary pancreatitis‐associated cationic trypsinogen mutants. (16th May 2013) - Geisz, Andrea; Hegyi, Péter; Sahin‐Tóth, Miklós
<x xml:space="preserve">Abstract</x> Mutations in human cationic trypsinogen cause hereditary pancreatitis by altering its proteolytic regulation of activation and degradation by chymotrypsin C (CTRC). CTRC stimulates trypsinogen autoactivation by processing the activation peptide to a shorter form, but also promotes degradation by cleaving the calcium‐binding loop in trypsinogen. Mutations render trypsinogen resistant to CTRC‐mediated degradation and/or increase processing of the activation peptide by CTRC. Here we demonstrate that the activation peptide mutations D19A, D22G, K23R and K23_I24insIDK robustly increased the rate of trypsinogen autoactivation, both in the presence and absence of CTRC. Degradation of the mutants by CTRC was unchanged, and processing of the activation peptide was increased fourfold in the D19A mutant only. Surprisingly, however, this increased processing had only a minimal effect on autoactivation. The tetra‐aspartate motif in the trypsinogen activation peptide binds calcium (KD of 1.6 mm), which stimulates autoactivation. Unexpectedly, calcium binding was not compromised by any of the activation peptide mutations. Despite normal binding, autoactivation of mutants D22G and K23_I24insIDK was not stimulated by calcium. Finally, the activation peptide mutants exhibited reduced secretion from transfected cells, and secreted trypsinogen levels were inversely proportional with autoactivation rates. We conclude that D19A, D22G, K23R and K23_I24insIDK form a mechanistically distinct subset of hereditary pancreatitis‐associated mutations that exert their effect primarily through direct stimulation of autoactivation, independently of CTRC. The potentially severe clinical impact of the markedly increased autoactivation is offset by diminished secretion, resulting in a clinical phenotype that is indistinguishable from typical hereditary pancreatitis.